National Social Service Scheme: Integration in Medical Education - Nath, Bhola; Kumari, Ranjeeta; Kamboj, Namita (Indian Journal of Community Health, 2014)
“I slept and dreamt that life was joy. I woke up and saw that life was service. I acted and behold, service was joy.”- Rabindranath Tagore National Service Scheme popularly known as “NSS” was launched on Mahatma Gandhi’s birth centenary year, 1969 under Ministry of Youth affairs and Sports, in 37 universities, involving students, with the primary aim to establish meaningful linkage between the campus and the community.